Analisis Putusan Perbuatan Melawan Hukum oleh PT. Bpr â€œArtha Wiwaha Arjunaâ€ Berdasarkan Undang-Undang Republik Indonesia Nomor 21 Tahun 2011 - Sefriyan Reynaldi; Cahaya Grace Roulina; Hana Juwita; Dwi Desi Yayi Tarina (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The unlawful act committed by PT. BPR "Artha Wiwaha Arjuna" against the plaintiffs, Inas Siati and Edi Subagya, involved a loan of IDR 300,000,000.00 secured by a Certificate of Ownership and a Mitsubishi vehicle registration certificate, which incurred drastically increasing fines. An analysis was conducted based on Article 1365 of the Civil Code, by examining the elements of an unlawful act, such as the existence of an unlawful act, the perpetrator's fault, the victim's loss, and the causal relationship between the act and the loss. In this case, the negligence of the Financial Services Authority (OJK) in carrying out its supervisory function over PT. BPR "Artha Wiwaha Arjuna" was also highlighted. Although the OJK has the authority to regulate the amount of fines, it did not act maximally because the case was already in court. The plaintiffs sued the OJK for this negligence. In conclusion, PT. BPR "Artha Wiwaha Arjuna" was proven to have committed an unlawful act, while the OJK was considered negligent in carrying out its supervisory function. It is recommended that the OJK improve its performance to avoid similar cases in the future.